2014
DOI: 10.1097/qad.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the alternatively spliced OPRM1 isoform μ-opioid receptor-1K in HIV-infected individuals

Abstract: Objective We previously examined the expression of specific C-terminal μ-opioid receptor (MOR) splice variants in human central nervous system cell types and HIV-infected brain tissue from subjects with neurocognitive impairment ± HIV encephalitis (HIVE). In the present study, we examined the N-terminal splice variant MOR-1K which mediates excitatory cellular signaling. Methods and Results We found segregation of expression ranging from undetectable to seemingly exclusive across nervous system cell types com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…The importance of 6-TM variants was further supported by recent studies showing the rescue of IBNtxA analgesia in knockout mice lacking 6-TM variants that were insensitive to IBNtxA by the lentiviral-mediated delivery of a 6-TM variant, mMOR-1G. It was reported that mMOR-1K, which exhibited excitatory cellular signaling, was elevated in HIV-infected individuals with combined neurocognitive impairment (NCI) and HIV encephalitis (HIVE) in relation to β-Adrenergic receptor and the inflammatory mediators MCP-1, MCP-2, and RANTES [62,63]. In addition, the 129S6 mice exhibited an analgesic response correlating to a measured decrease in MOR-1K gene expression levels, while CXB7/ByJ mice exhibited a hyperalgesic response correlating to a measured increase in MOR-1K gene expression levels, revealing that mMOR-1K contributes to the development of opioid-induced hyperalgesia [64].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of 6-TM variants was further supported by recent studies showing the rescue of IBNtxA analgesia in knockout mice lacking 6-TM variants that were insensitive to IBNtxA by the lentiviral-mediated delivery of a 6-TM variant, mMOR-1G. It was reported that mMOR-1K, which exhibited excitatory cellular signaling, was elevated in HIV-infected individuals with combined neurocognitive impairment (NCI) and HIV encephalitis (HIVE) in relation to β-Adrenergic receptor and the inflammatory mediators MCP-1, MCP-2, and RANTES [62,63]. In addition, the 129S6 mice exhibited an analgesic response correlating to a measured decrease in MOR-1K gene expression levels, while CXB7/ByJ mice exhibited a hyperalgesic response correlating to a measured increase in MOR-1K gene expression levels, revealing that mMOR-1K contributes to the development of opioid-induced hyperalgesia [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, selective MOR agonists such as endomorphin-1, but not DAMGO or morphine (Peterson et al, 1999) can increase HIV-1 replication in infected microglia—suggesting the involvement of a non-traditional MOR variant in HIV replication (Peterson et al, 1999) or suggesting that “biased agonism” (Hauser et al, 2012) may be operative. We have recently found that specific subsets of MOR splice variants, including MOR-1X and MOR-1K were differentially expressed by human astrocytes, but not expressed at detectable levels in microglia (Dever, Xu, Fitting, Knapp, & Hauser, 2012; Dever et al, 2014). Moreover, the expression of each MOR variant may be differentially regulated by HIV and in a cell specific manner (Dever et al, 2012; Dever et al, 2014).…”
Section: Microgliamentioning
confidence: 99%
“…We have recently found that specific subsets of MOR splice variants, including MOR-1X and MOR-1K were differentially expressed by human astrocytes, but not expressed at detectable levels in microglia (Dever, Xu, Fitting, Knapp, & Hauser, 2012; Dever et al, 2014). Moreover, the expression of each MOR variant may be differentially regulated by HIV and in a cell specific manner (Dever et al, 2012; Dever et al, 2014). Thus, microglia express a subset of MOR variants each of which may respond uniquely to morphine and/or HIV (Dever et al, 2012; Dever et al, 2014).…”
Section: Microgliamentioning
confidence: 99%
“…The MOR undergoes extensive alternative splicing and these splice variants may lead to cell-specific effects and unique pharmacological profiles [7880]. Increasing evidence has shown that MOR splice variants could directly affect HIV infection, susceptibility, and progression [78,79].…”
Section: Chemokine Receptor Bivalent Ligandsmentioning
confidence: 99%
“…The MOR undergoes extensive alternative splicing and these splice variants may lead to cell-specific effects and unique pharmacological profiles [7880]. Increasing evidence has shown that MOR splice variants could directly affect HIV infection, susceptibility, and progression [78,79]. When comparing the expression rates of three different MOR splice variants (MOR-1, MOR-1A, and MOR-1X), Dever et al found that they were differentially expressed in the individual CNS cell types [79].…”
Section: Chemokine Receptor Bivalent Ligandsmentioning
confidence: 99%